MEG3: a novel long noncoding potentially tumour-suppressing RNA in meningiomas - Balik, Vladimir; Srovnal, Josef; Sulla, Igor; Kalita, Ondrej; Foltanova, Tatiana; Vaverka, Miroslav; Hrabalek, Lumir; Hajduch, Marian (Journal of neuro-oncology, 2013)
Meningiomas represent one of the most common types of primary intracranial tumours. However, the specific molecular mechanisms underlying their pathogenesis remain uncertain. Loss of chromosomes 22q, 1p, and 14q have been implicated in most meningiomas. Inactivation of the NF2 gene at 22q12 has been identified as an early event in their pathogenesis, whereas abnormalities of chromosome 14 have been reported in higher-grade as well as recurrent tumours. It has long been supposed that chromosome 14q32 contains a tumour suppressor gene. However, the identity of the potential 14q32 tumour suppressor remained elusive until the Maternally Expressed Gene 3 (MEG3) was recently suggested as an ideal candidate. MEG3 is an imprinted gene located at 14q32 that encodes a non-coding RNA (ncRNA). In meningiomas, loss of MEG3 expression, its genomic DNA deletion and degree of promoter methylation have been found to be associated with aggressive tumour growth. These findings indicate that MEG3 may have a significant role as a novel long noncoding RNA tumour suppressor in meningiomas.
Keywords: RNA dlouhá nekódující; lidské chromozomy, pár 14; Meningioma; signální transdukce; nádory mozku; Neovascularization, Pathologic; Signal Transduction; Chromosomes, Human, Pair 14; meningeom; Humans; lidé; Brain Neoplasms; patologická angiogeneze; RNA, Long Noncoding